Exploration of Ethnomathematics in the Tahlilan Tradition of Sungai Malaya: Geometry and Beyond - Hodiyanto Hodiyanto; Abdillah Abdillah; Gemi Susanti; Rodríguez-Nieto Camilo Andrés; Ebenezer Bonyah (Pendidikan Matematika UNIMOR, 2026)
This study aims to explore the ethnomathematical elements embedded in the cultural practice of Tahlilan, particularly those related to geometric concepts. The research employed a qualitative approach with an ethnographic design. The participants consisted of community members directly involved in the implementation of Tahlilan, with the research conducted in settings where this tradition is commonly practised. Data were collected through observation, interviews, documentation review, and a literature study. The data were then analyzed through data reduction, data display, interpretation, and conclusion drawing. The findings indicate that Tahlilan is a religious and social tradition passed down across generations and continues to be preserved to this day. The practice involves a series of activities, including the preparation of traditional foods, repeated recitation of prayers, distribution of food packages (berkat), and social interactions among participants. The ethnomathematical aspects identified include representations of three-dimensional geometric solids in Tahlilan foods, such as cylinders, cones, truncated cones, and pyramids; number patterns reflected in the sequence of days of the Tahlilan observance; proportionality in the distribution of food; and combinatorial structures evident in the handshaking activities among participants. These findings demonstrate a strong connection between the cultural practice of Tahlilan and mathematical concepts, revealing the presence of mathematical thinking within community traditions. Furthermore, this study contributes to the development of culturally based mathematics learning, particularly in the areas of geometry.